2020
DOI: 10.1007/s40430-020-02375-6
|View full text |Cite
|
Sign up to set email alerts
|

Material removal analysis of hybrid EDM-assisted centrifugal abrasive flow machining process for performance enhancement

Abstract: Finishing of metallic machine components is a prime requirement for the better performance and longer product life cycle. To get highly finished machine components, a number of conventional and non-conventional finishing processes have evolved in recent times to overcome constraints due to shape and properties of materials. This paper discusses a new hybrid technique, Thermal additive centrifugal abrasive flow machining (TACAFM) which is a combination of centrifugal forceassisted abrasive flow machining and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 37 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…But in actual process, if the media flow in the gap is not continuous then it will develop oxide layers on the surface which could be clearly seen through figure 13(a). The development of oxide layers on the surface reduced the electrical conductivity of the workpiece which hampered the machining process due to lesser availability of thermal energy for melting [25]. This caused reduction in the material removal which might be a reason for the variation in experimental and modeling results.…”
Section: Validation Of the Model For Materials Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…But in actual process, if the media flow in the gap is not continuous then it will develop oxide layers on the surface which could be clearly seen through figure 13(a). The development of oxide layers on the surface reduced the electrical conductivity of the workpiece which hampered the machining process due to lesser availability of thermal energy for melting [25]. This caused reduction in the material removal which might be a reason for the variation in experimental and modeling results.…”
Section: Validation Of the Model For Materials Removalmentioning
confidence: 99%
“…Ali et al [24] used sharp CNT particles in addition to alumina as abrasive particles in the AFM process and found significant improvement in material removal and surface finish. In the latest development in AFM process, Ali et al [25] developed a Thermal additive Centrifugal Abrasive flow machining process in which the EDM process is hybridized with the Centrifugal force assisted AFM process. EDM process developed thermal effect over the workpiece surface which reduced the force required for indentation.…”
Section: Introductionmentioning
confidence: 99%
“…The material removal is done using three distinct modes such as micro-plowing, free rubbing, and micro-cutting (Kum et al, 2020;Dixit, Sharma, and Kumar, 2021c). The new surfaces in the abrasive machining process are created by random attacks of the abrasive elements over the irregularities that lie on the work surface (Walia, Shan, and Kumar, 2009;Ali et al, 2020). The extrusion pressure that is applied using the hydraulic cylinders generates the normal force as well as the "axial force" on the abrasive elements.…”
Section: Introductionmentioning
confidence: 99%
“…Chawla et al placed an electromagnet on the outer wall of the workpiece during AFM, and studied the in uence of magnetism on the effect of processing [12]. Ali et al studied the in uence of centrifugal force assisted AFM, and the experimental results showed that this method had a great bene cial effect on material removal and surface quality of the workpiece [13].…”
Section: Introductionmentioning
confidence: 99%